The formation of molecular hydrogen from water ice in the lunar regolith by energetic charged particles. Issue 6 (10th June 2013) - Jordan, A. P.; Stubbs, T. J.; Joyce, C. J.; Schwadron, N. A.; Spence, H. E.; Wilson, J. K.
Abstract : [1] On 9 October 2009, the Lunar Crater Observation and Sensing Satellite (LCROSS) mission impacted a spent Centaur rocket into the permanently shadowed region (PSR) within Cabeus crater and detected water vapor and ice, as well as other volatiles, in the ejecta plume. The Lyman Alpha Mapping Project (LAMP), a far ultraviolet (FUV) imaging spectrograph on board the Lunar Reconnaissance Orbiter (LRO), observed this plume as FUV emissions from the fluorescence of sunlight by molecular hydrogen (H2 ) and other constituents. Energetic charged particles, such as galactic cosmic rays (GCRs) and solar energetic particles (SEPs), can dissociate the molecules in water ice to form H2 . We examine how much H2 can be formed by these types of particle radiation interacting with water ice sequestered in the regolith within PSRs, and we assess whether it can account for the H2 observed by LAMP. To estimate H2 formation, we use the GCR and SEP radiation dose rates measured by the LRO Cosmic Ray Telescope for the Effects of Radiation (CRaTER). The exposure time of the ice is calculated by considering meteoritic gardening and the penetration depth of the energetic particles. We find that GCRs and SEPs could convert at least 1–7% of the original water molecules into H2 . Therefore, given the amount of water detected by LCROSS, such particle radiation‒induced dissociation of water ice could likely account for a significant percentage (10–100%) of the H2 measured by LAMP. Key Points: Energetic charged particles can form molecular hydrogen from lunar water ice